Giant Intrapulmonary Mature Teratoma with Thoracostomy Intervention: A Rare Case Report - Indriani, Sri Indah; Simatupang, Elvando Tunggul Mauliate; Bergant, Briliant; Makmur, Andreas; Rangkuti, Ina Farida (Universitaas Brawijaya, 2024)
Background: Teratoma usually found in mediastinum and rarely found in the lung. Mature teratomas are the most common histological type of germ cell tumours, followed by seminoma. First case reported by Mohr in 1839 and until now only few cases of intrapulmonary teratomas have been reported. Case: A man, 64-years old man, nonsmoker complains of shortness of breath since 6 months and worsened in a week. Patient had history medication for tuberculosis in 2019. Chest Contrast CT-Scan showed hypodense mass and suggestive for benign left lung tumor. TTNA were performed and suggestive for teratoma. Joint conference with several department agree to proceed with thoracostomy. Thoracostomy with wide excision been done to remove the mass and examined for anatomic pathology then confirmed for mature teratoma. During thoracostomy, we cannot removed 100% of the tumor because it adhesive with aorta and parietal pleura. Patient treated in ICU and worsens. Unfortunately, patient passed away four days later. Conclusion: Teratoma is rarely found inside of the lung. Early diagnosis and resection of intrapulmonary teratoma is critical to prevent complications and provide definitive treatment.